Indoor air quality and atopic sensitization in primary schools: A follow-up study - Cavaleiro Rufo, João (2017)
Background: The onset and exacerbation of allergic diseases and asthma have been associated with poorindoor air quality (IAQ) inside classrooms.Objective: The aim was to investigate how IAQ changed in primary schools after applying indoor air qualityrecommendations, and to explore how these changes influenced allergic sensitization on children.Methods: Total volatile organic compounds, PM2.5, PM10, CO2, CO, temperature and relative humidity inthe indoor and outdoor air of 20 primary schools were measured in 2010–2012. The school staff receivedinstructions on how to improve IAQ in accordance with the SINPHONIE guidelines. Atopy status wasassessed in children attending the participating classrooms by skin prick tests and exhaled nitric oxide.A follow-up sampling campaign was performed in 2014–2015 in the same schools.Results: Indoor PM2.5and PM10concentrations were approximately 40% lower in the follow-up mea-surements (p < 0.05). There were no significant differences regarding outdoor PM concentrations.Nevertheless, PM levels from the follow-up campaign still exceeded the reference value established byPortuguese legislation. Moreover, there were no significant differences in atopic prevalence and FENOvalues between the campaigns.Conclusion: These findings suggest that adoption of the recommendations based on the SINPHONIE guide-lines was particularly successful in reducing PM2.5and PM10in primary schools of Porto. Nevertheless,the schools failed to reduce the levels of other IAQ pollutants, as well as the prevalence of atopic disease.